2016
DOI: 10.2215/cjn.06290615
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Survival and Renal Recovery in Patients with Multiple Myeloma or Light-Chain Amyloidosis on Chronic Dialysis

Abstract: Background and objectives Monoclonal gammopathies (MGs) with renal involvement can lead to ESRD caused by myeloma cast nephropathy (MCN), immunoglobulin light chain amyloidosis (ALA), or light-chain deposition disease (LCDD). Few studies have focused on the prognosis of patients with MG on chronic dialysis. We evaluated the outcomes of patients with MG incident on chronic dialysis in France.Design, setting, participants, & measurements All incident patients registered in the Renal Epidemiology and Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 33 publications
2
48
0
7
Order By: Relevance
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40). Mobility status was assessed in all studies by using data on whether the patient was dependent for transfers and walking without objectifying actual mobility (for instance, by measuring gait speed).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Our interpretation of this finding is that it is likely to be an issue of selection bias and residual confounding: those fitter and more able, or better supported patients are more likely to choose a home‐based therapy than those less able and with less supportive home environment . There is little comparable published registry data on survival with ESKD and other plasma cell dyscrasia …”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether recent advances in myeloma therapy have translated to improved survival for all those with ESKD, and/or whether the new diagnostic and treatment paradigms for myeloma alter the characteristics of those who develop ESKD from their myeloma. Survival for people with ESKD and other plasma cell dyscrasia is less well characterized …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation